PENGARUH BERBALAS PANTUN UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI INTERPERSONAL MELALUI BIMBINGAN KELOMPOK SISWA KELAS X TKJ SMK LABOR BINAAN FKIP UNRI PEKANBARU - Fitriana Rahayu; Zulfan Saam; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of pantun reciprocated techniques on the improve interpersonal communication skills of students at the class X TKJ from the guided labor vocational school of the FKIP UNRI Pekanbaru. This type of research is quantitative research with the experimental method using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was the scale of interpersonal communication measurement which consisted of 37 items before validation, and after validation obtained 25 valid items with validity 0.4502 and reliability 0.849. The subjects of this study were 7 students who were identified as having low levels of interpersonal communication skills. The data analysis technique used is non parametric statistical techniques using the Rank Spearman test. The results of the study prove that the research hypothesis is accepted. Therefore, from the results of the Rank Spearman test, r = 0,926, while the correlation coefficient r2 is 0.857. Thus there is the influence of pantun reciprocated techniques on interpersonal communication skills by 86% in guided labor vocational school of the FKIP UNRI Pekanbaru. From the results of the Wilcoxon test obtained (Asymp.Sig) 0.018 <0.05 it can be concluded that there are differences in the scores of increased interpersonal communication skills before and after pantun reciprocated techniques are given.Key Words: Pantun Reciprocated, Interpersonal Communication